The Role and Implementation of the Administrative Court in Guaranteeing Legal Certainty in Government Administrative Decisions - Fitnawati WN, Santy; Maulana, Anas; Hidayatulloh, Syarif; Solehun, Solehun; Apitri, Siti (Fox Justi : Jurnal Ilmu Hukum, 2025)
The Administrative Court (Pengadilan Tata Usaha Negara, PTUN) holds a pivotal role in upholding the rule of law by reviewing the legality of state administrative actions and safeguarding citizens' legal rights. This study explores the existence and practical implementation of the PTUN in ensuring legal certainty over State Administrative Decisions (Keputusan Tata Usaha Negara, KTUN). Employing a normative juridical approach with qualitative-descriptive analysis, the research examines statutory regulations and relevant literature. The findings reveal that, despite a solid legal foundation, the effectiveness of PTUN is hindered by limited public legal awareness, restricted access to judicial mechanisms, and insufficient understanding of its jurisdictional authority. To enhance the court’s functionality within Indonesia’s administrative law system, the study recommends strengthening institutional frameworks, improving human resource capacity, and expanding public legal education. These measures are essential to realize the court's mandate in delivering administrative justice and ensuring good governance.